Persistent Abnormalities of Fatty Acids Profile in Children With Idiopathic Nephrotic Syndrome in Stable Remission - Turolo, Stefano; Edefonti, Alberto C.; Morello, William; Syren, Marie-Louise; De Cosmi, Valentina; Ghio, Luciana; Tamburello, Chiara; Demarco, Erika A.; Berrettini, Alfredo; Manzoni, Gianantonio; Agostoni, Carlo; Montini, Giovanni (Frontiers in Pediatrics, 2021)
Steroid-sensitive nephrotic syndrome is an immunological disorder mediated by still poorly defined circulating factor(s) that target the podocyte and damage the filtration barrier. Fatty acids (FA) have several biological roles and, in particular, are strictly involved in cell to cell communication, inflammatory processes and regulation of lymphocyte pools. Studies of FAs during INS have been mainly focused on biochemical changes during the phase of proteinuria; while no information is available about FA profile in patients with idiopathic nephrotic syndrome (INS) on stable remission. Aim of this study is to assess differences in blood FA profile between pediatric patients with INS during the phase of stable remission. Blood fatty acid profile of 47 pediatric patients on stable remission and 47 matched healthy controls were evaluated with gas chromatography. Patients with INS on stable remission had significantly higher levels of PUFA and omega-6 than controls (40.17 vs. 37.91% and 36.95 vs. 34.79%), lower levels of SFA and MUFA. Considering the single fatty acids, levels of omega-6 18:2n6 linoleic acid and omega-6 20:4n6 arachidonic acid were significantly higher in patients with INS than in controls (23.01 vs. 21.55%, p-value 0.003 and 10.37 vs. 9.65%, p-value 0.01). Moreover, patients with INS showed lower levels of SFA 14:0 (0.74 vs. 0.92%) and 18:0 (10.74 vs. 11.74%) and MUFA 18:1n9 oleic acid (18.50 vs. 19.83%). To the best of our knowledge this is the first study assessing FAs profile in children with INS in stable remission. In a population of 47 patients, we were able to demonstrate a higher blood level of linoleic and arachidonic acid, and consequently of omega-6 and PUFA, compared to controls. Persistently higher than normal levels of either linoleic or arachidonic acid, could be viewed as candidate biomarker for a state of risk of relapse in children with idiopathic nephrotic syndrome.